2005
DOI: 10.1051/0004-6361:20053389
|View full text |Cite
|
Sign up to set email alerts
|

A search for changing-look AGN in the Grossan catalog

Abstract: We observed with XMM-Newton 4 objects selected from the Grossan (1992, Ph.D. Thesis) catalog, with the aim to search for new "changinglook" AGN. The sample includes all the sources which showed in subsequent observations a flux much lower than the one measured with HEAO A-1: NGC 7674, NGC 4968, IRAS 13218+0552 and NGC 1667. None of the sources was caught in a high flux state during the XMMNewton observations, whose analysis reveal they are all likely Compton-thick objects. We suggest that, for all the sources,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 52 publications
6
78
0
Order By: Relevance
“…Fig. 6 shows the long-term X-ray light curve of NGC 7674 over a period of about 37 yr. As first noted by Bianchi et al (2005), the source showed a decline by a factor of ∼3 in the 2-10 keV band between the first detection by HEAO in the late 1970s and the Ginga measurement in 1989, followed by a further order of magnitude flux decrease in 1996 when BeppoSAX identified the source as a CTAGN (Malaguti et al 1998). Thereafter, the source flux has remained constant with no significant spectral or flux variation for the past ≈ 20 yr.…”
Section: The Soft X-ray Componentmentioning
confidence: 78%
See 4 more Smart Citations
“…Fig. 6 shows the long-term X-ray light curve of NGC 7674 over a period of about 37 yr. As first noted by Bianchi et al (2005), the source showed a decline by a factor of ∼3 in the 2-10 keV band between the first detection by HEAO in the late 1970s and the Ginga measurement in 1989, followed by a further order of magnitude flux decrease in 1996 when BeppoSAX identified the source as a CTAGN (Malaguti et al 1998). Thereafter, the source flux has remained constant with no significant spectral or flux variation for the past ≈ 20 yr.…”
Section: The Soft X-ray Componentmentioning
confidence: 78%
“…However, as discussed by Bianchi et al (2005), the background for the observation of NGC 7674 is based on a scanning observation obtained close in time to the target (Awaki et al 1991). These background scans result in noise estimates that are more reliable than model estimates typically adopted for non-imaging detectors.…”
Section: Background Uncertaintiesmentioning
confidence: 99%
See 3 more Smart Citations